2009
DOI: 10.1007/s00383-008-2310-x
|View full text |Cite
|
Sign up to set email alerts
|

The degree to which the size and side of an inguinal hernia is predictive of a hernia on the other side

Abstract: It is not possible to predict reliably which patients who present with a unilateral hernia would benefit from bilateral exploration, although the size of the hernia has a positive correlation with the size of the contralateral processus vaginalis/hernial sac. Those with "massive" hernias on the presenting side were more likely to have "large" contralateral hernial sacs, but how many of these would subsequently become symptomatic remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Larger hernias were more likely to recur, with ''massive'' ones recurring earlier than smaller hernias. Large hernial sacs more often occurred in small infants [13] and may be technically more difficult to repair. Thus, ''large'' and ''massive'' sacs were more likely to be opened during dissection, and those are seen predominantly in the youngest children.…”
Section: Discussionmentioning
confidence: 99%
“…Larger hernias were more likely to recur, with ''massive'' ones recurring earlier than smaller hernias. Large hernial sacs more often occurred in small infants [13] and may be technically more difficult to repair. Thus, ''large'' and ''massive'' sacs were more likely to be opened during dissection, and those are seen predominantly in the youngest children.…”
Section: Discussionmentioning
confidence: 99%
“…1 The incidence of the development of a metachronous hernia varies from 2.1 to 31% in the literature. 2,3 The routine exploration of the asymptomatic side in a unilateral inguinal herniotomy is therefore controversial. Benefits include prevention of a further anesthetic in the future, any complications associated with an untreated inguinal hernia such as incarceration, and the risks associated with another procedure.…”
Section: Metachronous Contralateral Pediatric Inguinal Herniamentioning
confidence: 99%
“…4 The prospective trials demonstrated a large range of MCIH incidence (2.3%-9.3%), as did the retrospective trials (2.1%-7.1%). 2,[5][6][7][8][9][10][11][12] When this evidence was combined in a new systematic review, an incidence of 6.4% in 31,164 pediatric patients was revealed (Table 1).…”
Section: Metachronous Contralateral Pediatric Inguinal Herniamentioning
confidence: 99%